Quality of life in transfusion-dependent thalassaemia patients on desferrioxamine treatment - Dahlui, M.; Hishamshah, M.I.; Rahman, A.J.A.; Aljunid, S.M. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2009)
Optimum desferrioxamine usage reduces iron overload complications and provides a better quality of life.